Improving medication optimisation in left ventricular systolic dysfunction after acute myocardial infarction. Issue 3 (28th August 2019) - Forsyth, Paul; Moir, Lynsey; Speirits, Iain; McGlynn, Steve; Ryan, Margaret; Watson, Anne; Reid, Fiona; Rush, Christopher; Murphy, Clare
Abstract : Glasgow city has the highest cardiovascular disease (CVD) mortality rate in the UK. Patients with left ventricular systolic dysfunction after acute myocardial infarction represent a 'high-risk' cohort for adverse CVD outcomes. The optimisation of secondary prevention medication in this group is often suboptimal. Our aim was to improve the use and target dosing of ACE inhibitors (ACEI), angiotensin II receptor blockers (ARBs) and beta-blockers in such patients, through pharmacist-led clinics and cardiology multidisciplinary team collaboration. Retrospective audits characterised baseline care. Prospective pharmacist-led clinics were piloted and rolled out across seven hospitals and primary care localities over four Plan–Do–Study–Act cycles. 'Hub' and 'spoke' clinics utilised independent prescribing pharmacists with different levels of cardiology experience. Pharmacists were trained through a bespoke training programme— 'Teach and Treat' . Consultant cardiologists provided senior support and governance. Patients attending prospective pharmacist-led clinics were more likely to be prescribed an ACEI (or ARB) and beta-blocker (n=856/885 (97%) vs n=233/255 (91%), p<0.001 and n=813/885 (92%) vs n=224/255 (88%), p=0.048, respectively) and be on target dose of ACEI (or ARB) and beta-blocker (n=585/885 (66%) vs n=64/255 (25%), p<0.001 and n=218/885 (25%) vs n=17/255 (7%), p<0.001, respectively) compared with baseline. The mean dose of ACEI (or ARB) and beta-blocker was also higher (79% vs 48% of target dose, p<0.001% and 48% vs 33% of target dose, p<0.001, respectively) compared with baseline. Use of secondary prevention medication was significantly improved by pharmacist and cardiology collaboration. These improvements were sustained across a 4-year period, supported by a novel approach called ' Teach and Treat ' which linked training to defined clinical service delivery. Further work is needed to assess the impact of the programme on long-term CVD outcomes.